Familial right ventricular dysplasia with biventricular involvement and inflammatory infiltration. Heart Muscle Disease Study Group. Issue 1 (July 1996) - Pinamonti, B.; Miani, D.; Sinagra, G.; Bussani, R.; Silvestri, F.; Camerini, F.
Abstract : The aetiology of right ventricular dysplasia/cardiomyopathy is presently unknown. A genetic background has been suggested, but myocarditis may play a part in its pathogenesis. Two familial cases of right ventricular dysplasia, one of whom had also a diagnosis of myocarditis, are reported. Both patients presented with ventricular arrhythmias. The father subsequently had a "flu-like" syndrome, heart failure, and biventricular dysfunction; "active" myocarditis was found at endomyocardial biopsy. Then the patient died suddenly. The daughter developed progressive biventricular dysfunction; then she was resuscitated from a cardiac arrest, and subsequently died suddenly. In both patients necropsy showed severe right ventricular atrophy and fibro-adipose substitution, associated with biventricular fibrosis. Inflammatory infiltration was also present in the first patient. This study shows the association of right ventricular dysplasia and myocarditis in the same family. These cases may represent a link between inherited and acquired ("inflammatory") forms of the disease.